Schizophrenia as failure of left hemisphere dominance for the phonological component of language - Angrilli, A; Spironelli, C; Elbert, T; Crow, T; Marano, G; Stegagno, L (Public Library of Science, 2009)
Background: T. J. Crow suggested that the genetic variance associated with the evolution in Homo sapiens of hemispheric dominance for language carries with it the hazard of the symptoms of schizophrenia. Individuals lacking the typical left hemisphere advantage for language, in particular for phonological components, would be at increased risk of the typical symptoms such as auditory hallucinations and delusions. Methodology/Principal Findings: Twelve schizophrenic patients treated with low levels of neuroleptics and twelve matched healthy controls participated in an event-related potential experiment. Subjects matched word-pairs in three tasks: rhyming/phonological, semantic judgment and word recognition. Slow evoked potentials were recorded from 26 scalp electrodes, and a laterality index was computed for anterior and posterior regions during the inter stimulus interval. During phonological processing individuals with schizophrenia failed to achieve the left hemispheric dominance consistently observed in healthy controls. The effect involved anterior (fronto-temporal) brain regions and was specific for the Phonological task; group differences were small or absent when subjects processed the same stimuli material in a Semantic task or during Word Recognition, i.e. during tasks that typically activate more widespread areas in both hemispheres. Conclusions/Significance: We show for the first time how the deficit of lateralization in the schizophrenic brain is specific for the phonological component of language. This loss of hemispheric dominance would explain typical symptoms, e. g. when an individual's own thoughts are perceived as an external intruding voice. The change can be interpreted as a consequence of "hemispheric indecision", a failure to segregate phonological engrams in one hemisphere.